ISLAMIC BANKING PERFORMANCE BASED ON BANK HEALTH BEFORE AND DURING THE COVID-19 - Suryani Sri Lestari; Siti Hasanah; Saniman Widodo; Mustika Widowati; Mella Katrinasari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The research entitled